Simultaneously presented animations facilitate the learning of higher-order relationships - Ploetzner, R.; Lowe, Ric (Elsevier, 2014)
In an experimental study, we investigated how the simultaneous and sequential presentation of animation episodes affects learners’ perceptual interrogation of the animation as well as their acquisition of higher-order relationships. Of the 60 students who participated in the study, 30 studied the animation episodes presented simultaneously and 30 studied the same episodes presented sequentially. The eye movements of eight participants from each group were recorded while they studied the animation episodes. The simultaneous presentation resulted in significantly more visual transitions between the episodes than the sequential presentation. Further, in case of the simultaneous presentation significantly more bi-directional visual transitions occurred than in case of the sequential presentation. Learning of higher-order relationships was significantly more successful from simultaneously presented episodes than from sequentially presented episodes.